(−)-Hinokinin Induces G2/M Arrest and Contributes to the Antiproliferative Effects of Doxorubicin in Breast Cancer Cells - Cunha, Nayanne Larissa; Teixeira, Gabriella Machado; Martins, Thomás Duzzi; Souza, Anderson Roberto; Oliveira, Pollyana Francieli; Símaro, Guilherme Venâncio; Rezende, Karen Cristina Souza; Gonçalves, Natália dos Santos; Souza, Daniel Gottardo; Tavares, Denise Crispim; Silva, Marcio Luís Andrade; dos Santos, Raquel Alves (Planta Medica, 2016)
Breast cancer incidence rises worldwide and new chemotherapeutical strategies have been investigated to overcome chemoresistance. (−)-Hinokinin is a dibenzylbutyrolactone lignan derived from the partial synthesis of (−)-cubebin extracted from Piper cubeba seeds. Biological effects of dibenzylbutyrolactone lignans include antiviral, antitumor, anti-inflammatory, and trypanocidal activities. In the present study, we evaluated the ability of (−)-hinokinin to modulate the antiproliferative effects of doxorubicin intumoral (MCF-7 and SKBR-3) and normal (MCF-10 A) breast cell lines. Treatment with (−)-hinokinin did not affect the cellular proliferation or contribute to the antitproliferative effects of doxorubicin in MCF-10 A cells. After 24 and 48 hours of treatment with (−)-hinokinin, MCF-7 and SKBR-3 were accumulated in G2/M and, when combined with doxorubicin, (−)-hinokinin contributed to the antiproliferative effects of this chemotherapic by modulation of the cyclin-dependent kinase inhibitor 1. Apoptotic cell death was observed in response to (−)-hinokinin alone in MCF-7, but not in SKBR-3 even 72 hours after treatment. In MCF-7, doxorubicin-induced apoptosis was not increased by (−)-hinokinin. The findings of the present study suggest (−)-hinokinin as an antiproliferative agent that contributes to the effects of doxorubicin. (−)-Hinokinin modulates apoptotic cell death via the molecular regulation of the cell cycle and apoptotic control genes, but the cellular genetic background directly affects the cell fate decision in response to treatment.
Keywords: (−)-hinokinin; breast cancer; cell proliferation; cell death; cell cycle